OPTIMALISASI NILAI TAMBAH DAN DIGITAL MARKETING PADA PRODUK OLAHAN BLIMBING DI DESA KALANGAN NGUNUT - Nailariza Umami; Maria Aghata Sri W.H.; Novita Eka Muliawati (JPM PAMBUDI, 2021)
The purpose of this social service was to optimize the potential development of fresh star fruits by increasing added value to increase innovation of star fruit processed products, brand and marketing strategies trhough digital marketing in Kalangan Village, Ngunut District. The methods used in this community service activity were lectures, discussions, demonstrations and direct practice. The work plan was programmed within 1 month. The results of this service activity are the increasing knowledge of community groups in Kalangan Ngunut Village in terms of digital marketing and innovation of starfruit processed products. Besides, people in Kalangan Ngunut village can directly practice digital marketing to promote starfruit products. In addition, they also can apply innovations to process fresh starfruit into processed products in the form of starfruit dates as well as package and label the product into more interesting way. In addition, the activities also increase public awareness to always improve innovation and strategies in building entrepreneurship in order to help their businesses to survive during the COVID-19 pandemic.